Effects of different dietary supplements combined with conditioning training on muscle strength, jump performance, sprint speed, and muscle mass in athletes: a systematic review and network meta-analysis - Beiwang Deng; Ruixiang Yan; Tianyuan He; Gesheng Lin; Ting Liu; Wen Chen; Jiaxin He; Duanying Li (Frontiers in Nutrition, 2025)
BackgroundAs dietary supplements have become integral to meeting athletes’ specialised nutritional requirements, research into their effects on performance has intensified. Yet inconsistent findings leave the efficacy of some supplements—most notably branched-chain amino acids and β-hydroxy-β-methylbutyrate (HMB)—open to debate. To clarify which products offer the greatest benefit, we undertook a systematic review and network meta-analysis aimed at identifying the supplements most effective for athletes, including protein, creatine, β-alanine, HMB, vitamin D, caffeine, and others.MethodsPubMed, Web of Science, the Cochrane Library, Embase and SPORTDiscus were searched from database inception to 15 March 2024 for RCTs evaluating the effects of dietary supplements (including but not limited to protein, creatine, β-alanine, HMB, caffeine, and vitamin D) on athletic performance. Risk of bias was appraised with the revised Cochrane RoB 2 tool. A network meta-analysis was performed in R.ResultsWe included 35 randomized controlled trials comprising 991 athletes who completed strength and conditioning training in conjunction with various dietary supplements or a placebo. The risk of bias assessment indicated that 8.57% of studies were at low risk, 88.57% had some concerns, and 2.86% were at high risk of bias. Protein supplementation yielded the greatest improvement in muscular strength (standardized mean difference [SMD] = 0.64, 95% confidence interval [CI] 0.31–0.97; surface under the cumulative ranking curve [SUCRA] = 99.6%; very low-certainty evidence). Both β-alanine (SMD = 0.41, 95% CI 0.10–0.72; SUCRA = 89.0%; moderate-certainty evidence) and creatine (SMD = 0.30, 95% CI 0.07–0.53; SUCRA = 76.06%; moderate-certainty evidence) significantly enhanced jump performance, with β-alanine ranking marginally higher. Creatine also reduced sprint time (SMD = −0.42, 95% CI − 0.68 to −0.16; SUCRA = 94.57%; moderate-certainty evidence). No supplement significantly increased lean body mass.ConclusionProtein supplementation appears to be the most effective strategy for increasing muscular strength; β-alanine and creatine both improve jump performance, with β-alanine offering marginally superior effectiveness; and creatine is particularly beneficial for sprint speed. As none of the supplements meaningfully increased muscle mass, practitioners should align supplementation strategies with the targeted performance attribute and training phase to optimise the synergy between nutrition and training and maximise athletic outcomes.Systematic review registrationPROSPERO, CRD420251048402.